FRAÇÕES QUÍMICAS DA MATÉRIA ORGÂNICA DO SOLO EM DIFERENTES SISTEMAS DE MANEJO NO MUNICÍPIO DE AQUIDAUANA, MS - SOUZA, Camila Beatriz da Silva; ROSSET, Jean Sérgio; FARIAS, Paulo Guilherme da Silva; PANACHUKI, Elói; OZÓRIO, Jefferson Matheus Barros; CASTILHO, Selene Cristina de Pierri (ANAIS DO ENIC, 2020)
-